2016
DOI: 10.1590/1806-9061-2016-0220
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a probiotic Containing Bacillus Subtilis on the Performance and Gut Health of Laying Japanese Quails (Coturnix Coturnix Japonica)

Abstract: Keywords Japanese quails, egg production, gut health, immune response. ABStRACtThe present study was carried out to determine the effects of the inclusion of a spore-forming probiotic (Bacillus subtilis) in laying Japanese quail diets as an alternative to growth-promoting antibiotics to help produce healthy eggs and meat. This experiment was conducted as a completely randomized design with three treatments (control, 0.05% bacitracin methylene disalicylate (BMD), or 0.1% Bacillus subtilis) of five replicates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
3
13
1
Order By: Relevance
“…Some differences between control and test groups were substantial but statistically insignificant, conceivably owing to the dependence of P values on sample sizes (Sullivan and Feinn, 2012), which were rather small in this study. However, there was a declining trend in the levels of T-CHOL and TG in the birds fed with a probiotic containing B. subtilis, which is consistent with the observations of Mahdavi et al (2005), Li et al (2011a) and Manafi et al (2016).…”
Section: Discussionsupporting
confidence: 90%
“…Some differences between control and test groups were substantial but statistically insignificant, conceivably owing to the dependence of P values on sample sizes (Sullivan and Feinn, 2012), which were rather small in this study. However, there was a declining trend in the levels of T-CHOL and TG in the birds fed with a probiotic containing B. subtilis, which is consistent with the observations of Mahdavi et al (2005), Li et al (2011a) and Manafi et al (2016).…”
Section: Discussionsupporting
confidence: 90%
“…In our previous in vitro studies, L. plantarum (Julendra et al, 2017) or S. cerevisiae (Istiqomah et al, 2018) as probiotics had been shown to possess cholesterol-lowering activity. The positive impact of probiotics on the performance of the laying quail was previously reported by several studies (Hosseini, 2011;Guclu, 2011;Manafi et al, 2016;Siadati et al, 2018). Kalsum et al (2012) reported that administration of L. fermentum did not influence egg quality parameters and egg weight, but significantly improved total egg production and lowered cholesterol content in egg yolk.…”
Section: Introductionsupporting
confidence: 52%
“…This finding was accordance to Kalsum et al (2012) who reported that administration of L. fermentum did not influence egg quality parameters (haugh unit, % egg albumen, % egg yolk and egg shell thickness) and egg weight. Manafi et al (2016) stated that the dietary inclusion of B. subtilis and BMD were not effecting the eggshell characteristics i.e., thickness, breaking strength, percentages, and also haugh unit. Zhong et al (2016) stated that supplementation of 0.3% yeast Kluyveromyces marxianus M3 strain on laying hen diet resulted in significant differences in the eggs nutrient composition (increase protein, crude fat level, and dry matter), weights, shell strength, albumen height, and haugh unit.…”
Section: Quality Of Quail Eggsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers found that feeding diets containing Bacillus subtilis decreased cecal E. coli count in Japanese quails (Manafi et al, 2016). Qureshi et al (1996) reported that SP had antimicrobial activity that improved chicken defence system.It was documented that the extract of SP was able to inhibit the growth of Klebsiellapneumoniae, Shigellashigae, E. coli, S. aureus, Proteus vulgaris, Pseudomonas aeruginosa and Salmonella typhi (Mala et al, 2009).The antibacterial activity of the algae extract could be due to the presence of different chemicals such as 1-Octadecene, 1-Heptadeceane (Mishra & Sree 2007), flavonoids, triterpenoids, phenolic compounds, fatty acids (Demule et al, 1996, Lampe et al, 1998, acrylic acid (Pradhan et al, 2014) free hydroxyl group (Yu et al, 2009).…”
Section: Ileal Microflora Populationmentioning
confidence: 99%